2013
DOI: 10.1016/j.plaphy.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Temporary reduction of radiation does not permanently reduce flavonoid glycosides and phenolic acids in red lettuce

Abstract: Applying transparent daytime screens in greenhouses in cool seasons reduces the amount of energy needed for heating, but also the solar radiation available for crops. This can reduce yield and product quality of leafy vegetables because of constrained photosynthesis and altered biosynthesis. To study this, we cultivated five-week old red leaf lettuce (Lactuca sativa L.) for four weeks in growth chambers under a photosynthetic photon flux density (PPFD) of 225 and 410 μmol m(-2) s(-1), respectively. Some plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 33 publications
4
40
1
1
Order By: Relevance
“…The red leaf lettuce is known to be rich in quercetins and chlorogenic acid (Crozier et al, 2000;Arabbi et al, 2004;Becker et al, 2013). Total phenols, chlorogenic acid and anthocyanin concentrations in the seedlings of this cultivar were found to be significantly higher under bluecontaining LEDs (Johkan et al, 2010).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The red leaf lettuce is known to be rich in quercetins and chlorogenic acid (Crozier et al, 2000;Arabbi et al, 2004;Becker et al, 2013). Total phenols, chlorogenic acid and anthocyanin concentrations in the seedlings of this cultivar were found to be significantly higher under bluecontaining LEDs (Johkan et al, 2010).…”
Section: Discussionmentioning
confidence: 84%
“…There may exist a direct link between blue light biosynthesis of certain phenylpropanoids through photosynthesis. Becker et al (2013) showed a close correlation between quercetin-glycosides concentrations with the reducing sugar concentration indicating that glucose might directly increase glucosylation of certain flavonoid aglycones to their glucosides. Accordingly, concentrations of two quercetin-glucosides increased in red leaf lettuce under supplemental blue light ( Table 2).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This result could be further justified by a previous study of the authors where significant differences between various ecotypes of C. spinosum were reported in terms of nutritional value and chemical composition. Similarly, Becker et al (2014Becker et al ( , 2013 reported that the effect of radiation intensity on phenolic compounds composition of lettuce plants is compound dependent and apart from environmental factors, plant ontogeny is also important. In another study, Pérez-López et al (2015) also observed that lettuce plants treated with high light intensities contained higher concentrations of carotenoids, glutathione, total phenols and anthocyanins, which was also the case in our study regarding total phenolic compounds content.…”
Section: Tablementioning
confidence: 98%
“…Moreover, Bonasia et al (2017) have reported seasonal differences in visual quality and nutritional profile of wild rocket, with colder periods (autumn-winter) resulting in better visual quality, whereas warmer periods (winterspring) were beneficial to nutritional profile in terms of nitrates, total phenols, ascorbic acid and glucosinolates content. According to Becker et al (2014), light intensity and growth stage may affect phenolic compounds composition, such as cyanidin and quercetin glucosides in lettuce plants grown under shading nets, while Becker et al (2013) reported that the reduction of flavonoid glycosides content under low light intensities is fully compensated when plants are subsequently subjected to high photosynthetic photon flux density. Moreover, other phenolic compounds such as caffeic acid derivatives were not affected by shading conditions (Becker et al, 2014), which indicates that apart from environmental factors, ontogeny is also important for chemical composition of leafy vegetables.…”
Section: Introductionmentioning
confidence: 99%